A binational registry of adults with pulmonary arterial hypertension complicating congenital heart disease. Issue 9 (September 2015) - Strange, G.; Rose, M.; Kermeen, F.; O'Donnell, C.; Keogh, A.; Kotlyar, E.; Grigg, L.; Bullock, A.; Disney, P.; Dwyer, N.; Whitford, H.; Tanous, D.; et al.
Abstract Background The management of children with congenital heart disease (CHD) has improved over recent decades and several patients surviving with CHD into adulthood are increasing. In developed countries, there are now as many adults as there are children living with CHD. Pulmonary arterial hypertension (PAH) occurs in ∼5% of patients with CHD. Aim We aimed to understand the characteristics and outcomes of this emerging population. Methods We collected data retrospectively and prospectively from 12 contributing centres across Australia and New Zealand (2010–2013). Patients were included if they had been diagnosed with PAH and CHD and had been seen once in an adult centre after 1 January 2000. Results Of 360 patients with CHD‐PAH, 60% were female and 90% were New York Heart Association functional class II or III at the time of adult diagnosis of PAH. Mean age at diagnosis of PAH in adulthood was 31.2 ± 14 years, and on average, patients were diagnosed with PAH 6 years after symptom onset. All‐cause mortality was 12% at 5 years, 21% at 10 years and 31% at 15 years. One hundred and six patients (30%) experienced 247 hospitalisations during 2936 patient years of follow up. Eighty‐nine per cent of patients were prescribed PAH specific therapy (mean exposure of 4.0 years). Conclusions Adults with PAH and CHD often have this diagnosis made after significant delay, and have substantial medium‐term morbidity and mortality. This suggests a need for children transitioning to adult care with CHD to be closely monitored for this complication.